Oxidation‐Resistant, Cost‐Effective Epoxide‐Modified Polyamine Adsorbents for CO2 Capture from Various Sources Including Air. Issue 8 (1st April 2019) - Goeppert, Alain; Zhang, Hang; Sen, Raktim; Dang, Huong; Prakash, G. K. Surya
Abstract: CO2 adsorbents based on the reaction of pentaethylenehexamine (PEHA) or tetraethylenepentamine (TEPA) with propylene oxide (PO) were easily prepared in "one pot" by impregnation on a silica support in water. The starting materials were readily available and inexpensive, facilitating the production of the adsorbents on a large scale. The prepared polyamine/epoxide adsorbents were efficient in capturing CO2 and could be regenerated under mild conditions (50–85 °C). They displayed a much‐improved stability compared with their unmodified amine counterparts, especially under oxidative conditions. Leaching of the active organic amine became minimal or nonexistent after treatment with the epoxide. The adsorption as well as desorption kinetics were also greatly improved. The polyamine/epoxide adsorbents were able to capture CO2 from various sources including ambient air and indoor air with CO2 concentrations of only 400–1000 ppm. The presence of water, far from being detrimental, increased the adsorption capacity. Their use for indoor air quality purposes was explored. Abstract : Removing CO2 from air : The stability of polyamine‐based CO2 adsorbents is improved dramatically by their simple and easy chemical modification with epoxides. These low‐cost polyamine/epoxide composites impregnated on a silica support are very efficient at capturing CO2 repeatedly under mild conditions even from ambient air with CO2 concentrations of 400–1000 ppm.